Potential of Hydrogel Acemannan Aloe Vera (Aloe vera) on Wound Healing After Tooth Extraction In vivo Via Regulation of Inflammatory Response - Firdha Muharraran; Gusbakti Rusip; Rosa Paradita Dalimunthe (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Tooth extraction is a surgical procedure that involves hard tissue such as bone and soft tissue. Wounds on soft tissue are then followed by a healing process that occurs through three phases, namely the inflammatory phase, the proliferative phase, and the remodeling phase. Acemannan has the ability to stimulate hematopoiesis and antioxidant effects. Acemannan is able to reduce inflammation through prostaglandin synthesis and increase leukocyte infiltration and play a significant role in the oral wound healing process. Methods: This study is an in vivo experimental study. A total of 30 rats (5 each/group) were divided into groups that received 1%, 2%, 4%, 8%, povidone-iodine, and carbopol acemannan Aloe vera hydrogel. Furthermore, the number of macrophage cells in the tissue after tooth extraction was assessed. Data analysis was carried out with the help of SPSS with ANOVA and post hoc LSD tests. Results: There was a significant difference between the application of acemannan 1% hydrogel and 4% acemannan hydrogel, 8%, povidone-iodine, and carbopol, between the application of acemannan 2% hydrogel 4% acemannan hydrogel, 8%, povidone-iodine and carbopol, applications acemannan hydrogel 8% with carbopol, and between povidone-iodine and carbopol (p≤0.05). Conclusion: Acemannan Aloe vera hydrogel is able to accelerate wound healing after tooth extraction in vivo by suppressing macrophage cell activity.